Granice błędu – norma językowa a teksty prawne - Moroz, Andrzej (Poznańskie Spotkania Językoznawcze, 2014)
A material basis for the conducted considerations are the texts of the selected legal acts. The aim is to diagnose the principle causes favouring the deviations from the binding language norms in such texts. Thus, the analyses try to demonstrate that such language flaws as ellipticalness of utterances, an excessive number of lexical repetitions or the formation of non-standard syntactical collocations need not be the token of linguistic imperfection of a legal text (its incorrectness), but the result of complex legislative procedures visible in the processes of terminologization, synonymy, message economy or message openness. Due to this, the opinions about linguistic correctness of legal texts are not always evident and determining the boundaries of error is not always explicit.